2020
DOI: 10.1038/s41467-020-15943-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model functionalization of disease-associated PTEN missense mutations identifies multiple molecular mechanisms underlying protein dysfunction

Abstract: Functional variomics provides the foundation for personalized medicine by linking genetic variation to disease expression, outcome and treatment, yet its utility is dependent on appropriate assays to evaluate mutation impact on protein function. To fully assess the effects of 106 missense and nonsense variants of PTEN associated with autism spectrum disorder, somatic cancer and PTEN hamartoma syndrome (PHTS), we take a deep phenotypic profiling approach using 18 assays in 5 model systems spanning diverse cellu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 72 publications
3
41
0
Order By: Relevance
“…If a dominant negative process is operating, it may suggest that early interventions that focus on degrading mutant PTEN could be a useful strategy in some cases. Recent work has demonstrated substantial variability in impact on PTEN protein stability and function across different missense mutations [ 48 , 49 , 51 ]. This suggests that the above-described pattern of modest reduction in PTEN levels may mask substantial variability, potentially explaining the observed heterogeneity of outcomes across PTEN mutation cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a dominant negative process is operating, it may suggest that early interventions that focus on degrading mutant PTEN could be a useful strategy in some cases. Recent work has demonstrated substantial variability in impact on PTEN protein stability and function across different missense mutations [ 48 , 49 , 51 ]. This suggests that the above-described pattern of modest reduction in PTEN levels may mask substantial variability, potentially explaining the observed heterogeneity of outcomes across PTEN mutation cases.…”
Section: Discussionmentioning
confidence: 99%
“…Samples sizes were also insufficient to evaluate the functional impact of missense mutations in PTEN patients [ 51 ]. Future work in larger samples, computing fitness [ 48 ] and abundance [ 49 ] scores and identifying candidate dominant negative mutations, will be crucial to understanding whether different mutations influence peripheral protein levels and/or neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics studies suggested that functional consequences of missense mutations can be predicted based on structural features for the ASD-and cancer-associated protein phosphatase PTEN as well as for voltage-gated sodium and calcium channels (Heyne et al, 2020;Smith, Thacker, Jaini, et al, 2019;Smith, Thacker, Seyfi, et al, 2019). However, to our knowledge, studies correlating distinguishable structural perturbations of disease-relevant protein missense variants with an altered cellular phenotype are very limited (Post et al, 2020). In this work, we found that missense mutation induced impairments of the structural integrity of SHANK3 serve as molecular starting point for higher order pathogenic processes associated with ASD.…”
Section: Asd-associated Shank3 Missense Variants Exhibit Distinguishable Structural Perturbations On Secondary Tertiary and Quaternary Stmentioning
confidence: 99%
“…Importantly, tumours driven by these, as well as other loss-of-function Pten mutations, often present with more advanced malignant features and display increased levels of AKT activation compared to Pten +/− tumours. Mechanistically, upon dimerisation, PTEN mutations inhibit the function of the remaining wild-type protein and promote tumourigenesis in a dominant negative manner [42][43][44].…”
Section: Ptenmentioning
confidence: 99%